Clinical Auditing of Patient Safety Standards Before and After Implementation of the Training Program in Intensive Care Units - Bayatmanesh, Habibeh; Zagheri Tafreshi, Mansoureh; Manoochehri, Houman; Akbarzadeh Baghban, Alireza (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Patient safety is the precious core in the healthcare organizations aimed at minimizing adverse events and eliminating preventable damages. This study aimed at determining the rate of observation of safety standards of ICU patients by nurses before and after implementation of a training program. Methods: This quasi-experimental single-group study was conducted in two phases: observation of nursing performance related to patient safety and the implementation of a corrective training program. In the first phase, 4104 cases of nursing care related to patient safety performed by 54 ICU nurses were observed using chronological sampling. The same samples, i.e., 4104 nursing care performed by the same nurses, were used in the second phase of the study after implementing the training program. The data collection instrument was a valid and reliable researcher-made 76-item questionnaire consisting of 12 categories about nursing care related to patient safety. The corrective training program focused on nursing care related to patient safety. The gleaned data were analyzed with SPSS18 using descriptive statistics and non-parametric Wilcoxon signed-rank tests. Results: The rate of correspondence between nursing care and the checklist was 44.32 % before the intervention, which increased to 95.61% after intervention by a 51.29% increase. Conclusions: Implementation of the corrective intervention effectively promotes patient safety as a training program for nurses. The healthcare system's managers and authorities can reduce the damages sustained by patients and decrease treatment costs by concentrating on periodic supervision and continuous education programs to improve patient safety.